2017
DOI: 10.1097/brs.0000000000002105
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Function Does Not Improve 2 Years After Posterior Surgical Correction of Adolescent Idiopathic Scoliosis

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…As the scoliosis patients at the LPO presented higher VR values, we suggested that ventilatory limitation may be the cause or contribute to exercise intolerance. 24 Although restrictive ventilatory disorders are described as frequent in AIS patients, 25 especially in curvatures greater than 45º, 5 we observed that even with slight residual curvatures after the surgical procedure, patients presented significantly lower FVC and FEV 1 values when compared to the CG. Studies have found increased pulmonary function (FVC and FEV 1 ) two years after the surgical procedure in AIS patients.…”
Section: Discussionmentioning
confidence: 64%
“…As the scoliosis patients at the LPO presented higher VR values, we suggested that ventilatory limitation may be the cause or contribute to exercise intolerance. 24 Although restrictive ventilatory disorders are described as frequent in AIS patients, 25 especially in curvatures greater than 45º, 5 we observed that even with slight residual curvatures after the surgical procedure, patients presented significantly lower FVC and FEV 1 values when compared to the CG. Studies have found increased pulmonary function (FVC and FEV 1 ) two years after the surgical procedure in AIS patients.…”
Section: Discussionmentioning
confidence: 64%
“…Seeking to understand the pre-and postoperative tolerance of individuals with AIS for aerobic exercise, it was possible to verify only three studies in the literature. [18][19][20] These studies did not report improved tolerance for exercise following AIS deformity correction surgery during two years of postoperative follow-up, and for this analysis the authors used the cardiopulmonary exercise test to measure the maximum oxygen consumption (VO 2 max) of the participants. The research that most resembles our study was developed by Araujo et al, 36 in which the authors evaluated tolerance for exercise in AIS patients in the postoperative period with a control group of healthy adolescents, using the incremental shuttle walk test (ISWT).…”
Section: Resultsmentioning
confidence: 99%
“…15,16 In this context, little is known about the effect of deformity correction surgery on exercise tolerance in AIS patients. [18][19][20] Lenke et al 18 were the first to evaluate ventilatory efficiency during physical exercise in patients with AIS submitted to deformity correction surgery and found no improvement in ventilatory efficiency in most patients. Subsequently, Jeans et al 19 and Lorente et al 20 also observed low cardiorespiratory tolerance for maximum physical exercise and no improvement following corrective surgery.…”
Section: Introductionmentioning
confidence: 99%
“…A possible hypothesis is that the functional respiratory limitations described in patients with severe Scheuermann’s hyperkyphosis would benefit from surgical correction of the sagittal deformity. This issue has already been evaluated in patients with severe AIS who showed a limited tolerance to maximal cardiorespiratory exercise before surgery 4 . Both VO 2 max and VEmax remained essentially unchanged 2 years after surgical correction.…”
Section: Introductionmentioning
confidence: 99%